Computer Network Security: A Review And Implementation For Beginner Users - Muhammad Farhan; Rudi Arif Candra; Ihsan Anwar; Fardiansyah Fardiansyah; Dina Miftahul Jannah; Devi Satria Saputra (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
Computer network security has become a crucial aspect in the digital era as users increasingly depend on network technologies for daily activities. Beginner users represent one of the most vulnerable groups to cyber security threats due to limited technical knowledge and low security awareness. This article aims to provide a comprehensive review of fundamental concepts, common threat types, and basic network security strategies that are relevant for beginner users. The research method employed is a descriptive literature review of scientific articles and academic publications related to computer network security published between 2018 and 2025. The collected literature was analyzed to identify dominant threats and effective protection mechanisms for beginner users. The results indicate that threats such as malware, phishing, ransomware, and unauthorized access remain major security issues. The implementation of basic security mechanisms, including strong password policies, firewalls, antivirus and anti-malware software, regular system updates, and improved user awareness, has proven effective in minimizing security risks. With adequate understanding and proper implementation of these measures, beginner users are expected to apply network security practices more safely, responsibly, and efficiently.